Study of Operational and Maintenance Costs for Public Bus Transport - Kusuma, Catra Editya; Dewantoro, Fajar (JTI: Jurnal Teknik Industri, 2024)
Public transportation is a means of transportation for travelling and carrying out daily activities, and it has become one of the community's transportation needs. This research also aims to determine vehicle operational costs and maintenance costs incurred. This research was conducted on the PT Sriwijaya Pratama Express economy bus. The data obtained from this research are the results of interviews with the bus and interviews with the company. The data obtained includes vehicle depreciation, vehicle interest capital, engine oil prices, fuel prices, tyre usage, maintenance wages and bus crew wages. Based on this data, fixed costs, variable costs and overhead costs can be obtained. For fixed costs, the result is IDR 515.64 per km. Non-fixed costs are IDR 4,867.57 per km and overhead costs are IDR 1,076.64 per km. Details such as minor servicing carried out every 10,000 km and major servicing carried out every 20,000 km are also routinely carried out by PT. Sriwijaya Pratama Express. Keywords: Public transportation, BOK, Maintenance.